Female ornaments: is red skin color attractive to males and related to condition in rhesus macaques? - William Allen (Behavioral Ecology, 2021)
Sexual selection produces extravagant male traits, such as colorful ornaments, via female mate choice. More rarely, in mating systems in which males allocate mating effort between multiple females, female ornaments may evolve via male mate choice. Females of many anthropoid primates exhibit ornaments that indicate intraindividual cyclical fertility, but which have also been proposed to function as interindividual quality signals. Rhesus macaque females are one such species, exhibiting cyclical facial color variation that indicates ovulatory status, but in which the function of interindividual variation is unknown. We collected digital images of the faces of 32 rhesus macaque adult females. We assessed mating rates, and consortship by males, according to female face coloration. We also assessed whether female coloration was linked to physical (skinfold fat, body mass index) or physiological (fecal glucocorticoid metabolite [fGCM], urinary C-peptide concentrations) condition. We found that redder-faced females were mated more frequently, and consorted for longer periods by top-ranked males. Redder females had higher fGCM concentrations, perhaps related to their increased mating activity and consequent energy mobilization, and blood flow. Prior analyses have shown that female facial redness is a heritable trait, and that redderfaced females have higher annual fecundity, while other evidence suggests that color expression is likely to be a signal rather than a cue. Collectively, the available evidence suggests that female coloration has evolved at least in part via male mate choice. Its evolution as a sexually selected ornament attractive to males is probably attributable to the high female reproductive synchrony found in this species.